Fall in Haemophilus influenzae serotype b (Hib) disease following implementation of a booster campaign. Issue 8 (17th October 2007) - Ladhani, S; Slack, M P; Heys, M; White, J; Ramsay, M E
Abstract : Objective: To assess the impact of a Hib vaccination booster campaign targeting children aged 6 months to 4 years between May and September 2003, following a nationwide increase in the number of invasive Haemophilus influenzae serotype b (Hib) cases in all age groups after 1999. Design: The Health Protection Agency Centre for Infections prospectively monitors all cases of H influenzae disease in England and Wales and collects data from primary care trusts (PCTs) on coverage for vaccines in the childhood programme. Population: Adults and children in England and Wales (January 1991 to December 2006) Results: Data on vaccine coverage during the Hib booster campaign were available for 288/303 (95%) PCTs in England and revealed coverage of 71.8% for the 6–12-month age group and 63.2% for the 13–48-month age group. The Hib booster campaign resulted in a dramatic reduction in cases within 12 months in the age groups targeted for the booster. This decline was followed by a reduction in the number of cases reported among older children and adults. Since the campaign, however, there has been an increase in the number of cases reported among 1–3-year-old children (13 cases in 2004, 26 cases in 2005 and 32 cases in 2006), primarily in children who were too young to be vaccinated in the booster campaign. This group of children will be targeted in the pre-school catch-up programme that began in September 2007. Conclusions: The Hib booster campaign has helped to re-establish herd immunity in the UK. The increase in Hib disease among toddlers after 2004 supports the decision to introduce routine boosting for Hib at 12 months of age.